Corporate environmental information disclosure and bank financing: Moderating effect of formal and informal institutions. (23rd March 2022) - Li, Qiang; Ruan, Wenjuan; Shi, Huimin; Xiang, Erwei; Zhang, Feida (Frank)
Abstract: This paper investigates the effect of the quality of environmental information disclosure of firms on their bank financing and further examines the moderating effect of formal and informal institutions on this effect using China as a laboratory. We find that the quality of environmental information disclosure is positively (negatively) related to the scale (cost) of bank financing. Furthermore, the formal institution (proxied by the official issuance of the Green Credit Guidelines ) strengthens the above relationship. Moreover, the informal institution (proxied by bank connection) weakens the association between the quality of environmental information disclosure and bank financing. Our results are valid after addressing the potential endogeneity between environmental information disclosure and bank financing and remain unchanged in various robustness tests. Our findings affirm the decision usefulness of corporate environmental information disclosure that can be used by companies as an effective strategy for obtaining bank financing and the ethical integrity of borrowers to banks as an important group of capital market participants.